Synthesis, characterization, and antimicrobial and antiproliferative effects of CuO-TiO2-chitosan-escin nanocomposites on human leukemic MOLT4 cells - Elderdery, Abozer Y.; Alhamidi, Abdulaziz H.; Elkhalifa, Ahmed M. E.; Althobiti, Maryam M.; Omer, Nawal Eltayeb; Alsugoor, Mahdi H.; Alsuhaymi, Naif; Atebien, Entesar M.; Hamza, Siddiqa M. A.; Alzahrani, Badr; Alanazi, Fehaid; Kumar, Suresh S.; et al. (Multidisciplinary Digital Publishing Institute, 2022)
Nanocomposites comprised of CuO-TiO2-chitosan-escin, which has adjustable physicochemical properties, provide a solution for therapeutic selectivity in cancer treatment. By controlling the intrinsic signaling primarily through the mitochondrial signaling pathway, we desired nanocomposites with enhanced anticancer activity by containing CuO-TiO2-chitosan-escin. The metal oxides CuO and TiO2, the natural polymer chitosan, and a phytochemical compound escin were combined to form CuO-TiO2-chitosan-escin nanocomposites. The synthesized nanocomposites were confirmed and characterized using FTIR spectroscopy, TEM, and UV-Vis absorption spectroscopy. A human leukemia cell line (MOLT-4) was used to assess the efficacy and selectivity of nanocomposites. Based on a cytotoxicity study, CuO-TiO2-chitosan-escin nanocomposites had inhibition concentrations (IC50) of 13.68, 8.9, and 7.14 µg/mL against human T lymphoblast cells after 24, 48, and 72 h of incubation, respectively. Compared with untreated MOLT-4 cells, CuO-TiO2-chitosan-escin nanocomposite-treated cells significantly increased (p < 0.05) caspase-3, -8, and -9 and decreased the levels of antioxidant enzymes GR, SOD, and GSH. Furthermore, MDA for lipid peroxidase and ROS levels significantly increased (p < 0.05) in the treated cells than in the untreated cells. Remarkably, CuO-TiO2-chitosan-escin nanocomposite-mediated control of cell cycles were mainly achieved through the activation of caspase-3, -8, and -9.